Does the Covid-19 Pandemic Affect the Stock Market in Indonesia? - Dwi Rahmayani; Shanty Oktavilia (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2020)
This study aimed to analyze the existence and effect of the Covid-19 pandemic on the stock market over the long-term and short-term in Indonesia. The study followed Krugman’s (1979) approach stating the pandemic crisis problems have the potential to decrease the performance of the international balance of payments which will ultimately lead to uncertainty in the market. The research method was the Error Correction Model (ECM) with stock markets as an endogenous variable; and exchange rate, inflation, interest rate, foreign stock markets, commodity price, and pandemic as exogenous variables. The pandemic indicator was measured by total accumulative cases of Covid-19 per day in Indonesia. Using ECM, the result showed that foreign interest rates and commodity prices positively affect the stock markets. Conversely, the exchange rate has a negative effect on the stock markets. However, the estimation fails to reflect the significant impact of the Covid-19 pandemic in the short-term, but it has a negative effect on stock markets in the long-term. This result implies that the higher total accumulative cases of Covid-19 has been the source of Indonesia’s stock market weakness in the long-term. To the best of the author’s knowledge, this study is the first to examine Indonesia’s stock market’s pandemic impact between the short term and long term.